2017
DOI: 10.7196/sajog.2017.v23i1.1059
|View full text |Cite
|
Sign up to set email alerts
|

Puerperas’ knowledge regarding postpartum exercises in a tertiary hospital in the Capricorn District of Limpopo Province, South Africa

Abstract: RESEARCHBackground. Postpartum exercises (PPEs) are critical for the involution process post delivery. PPE affects the physical and psychological wellbeing of puerperas. Clinical observation shows a lack of exercise by puerperas in postnatal units. Objectives. To determine puerperas' knowledge regarding PPE, as well as to develop a health education programme on PPE. Methods. A quantitative, non-experimental, descriptive research design was employed. Probability random sampling was used to ensure that all puerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
(11 reference statements)
1
5
0
1
Order By: Relevance
“…On the control group, the median is 44 which is in category 3 or moderately dependent with the standard of 41-60%. The control group was influenced by several factors such as knowledge, age, culture, motivation, mother's experience, principal beliefs, and fatigue level (Mbombi et al, 2017). The test reveals that the p value is 0.000 (<0.05) which shows that there is a difference in the perineal care independency on the treatment group with Android app education using BUBI Care compared to the control group who did not use the app (Komariah, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the control group, the median is 44 which is in category 3 or moderately dependent with the standard of 41-60%. The control group was influenced by several factors such as knowledge, age, culture, motivation, mother's experience, principal beliefs, and fatigue level (Mbombi et al, 2017). The test reveals that the p value is 0.000 (<0.05) which shows that there is a difference in the perineal care independency on the treatment group with Android app education using BUBI Care compared to the control group who did not use the app (Komariah, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These postpartum mothers have and can operate the smartphone well. The BUBI Care app contains materials like perineal care that is aimed at helping postpartum mothers to care for themselves independently with their own capabilities, raising their self esteem (Mbombi et al, 2017). There is a need for caring that can be done, like having empathy, showing concern and providing care with competent capabilities, providing a sense of security and comfort that can help provide opportunities to encourage mothers becoming independent in performing confident and positive perineal care.…”
Section: Introductionmentioning
confidence: 99%
“…He found that very low percentage of the mothers had adequate knowledge regarding the postpartum exercise and added that there is a need for educational interventions regarding postpartum exercise among puerperas. Second, Mbombi, et al [11] who had evaluated puerperas' knowledge regarding postpartum exercise in South Africa. Found that there was lacked knowledge regarding postpartum exercise and a high rate of ignorance among postnatal mothers regarding the importance of postpartum exercise.…”
Section: Discussionmentioning
confidence: 99%
“…So a sustainable educational programme should be developed by the registered nurses on postpartum physical exercise in postnatal units. [11] Comprehensive exercise programs that focuses on muscular strength, endurance, and flexibility plays a vital role in women's health and wellbeing. [12] Many researches indicate the successful use of Trans-theoretical Model (TTM ) based interventions to develop most of health behaviors among different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Sehingga pada otot abdomen tersebut terjadi peningkatan aliran darah otot yang berakibat proses transportasi oksigen dan nutrisi yang dibutuhkan tubuh juga meningkat, sehingga memberikan kekuatan pada otot berkontraksi secara maksimal. Penguatan otot tranversus abdominis merupakan latihan penguatan untuk menjaga otot abdomen bagian tranversal agar lebih kuat yang dilakukan oleh ibu nifas setelah melewati peregangan selama kehamilan dan proses persalinan (Mbombi, Thopola, & Kgole, 2017).…”
Section: Pendahuluanunclassified